DIVINE ASPECTS IN POETRY “SUBUH” AND “PANGGILAN PAGI MINGGU” POET PUJANGGA BARU: ASPEK KETUHANAN DALAM PUISI “SUBUH” DAN “PANGGILAN PAGI MINGGU” PENYAIR PUJANGGA BARU - Alya Rahayu Pratiwi; Yusup Tanjung Nugroho; Yosi Wulandari (Jurnal Kata, 2023)
The objectives of this study are, (1) to describe the form of the hierarchy of needs in the novel Nyala Semesta by Farah Qoonita and (2) to describe the character of Khalid in the novel. This research is a descriptive method, which describes the situation of how the fulfillment of the hierarchy of needs carried out by Khalid's character. The approach used is the literary psychology approach. The technique used in data collection is literature study. The data analysis technique is content analysis. Based on the results of the analysis of the novel Nyala Semesta by Farah Qoonita, a multilevel hierarchy of needs was found in Khalid's character, including physiological needs in the form of air and food; security needs in the form of peace, security and protection; love and belonging needs in the form of affection; self-esteem needs in the form of status, self-esteem, and authority; self-actualization needs in the form of new experiences, kinship, ethics, humility, and attention. The character of Khalid includes compassion, hard work, patience, firmness, loyalty, curiosity.